DESIGN OF SPEED CONTROL BRUHLESS DC MOTOR BASED POWER FACTOR CORRECTION (PFC) USING SINGLE ENDED PRIMARY INDUCTANCE CONVERTER (SEPIC) - Nanda Redha Arsya; Heri Suryoatmojo; Sjamsjul Anam (Jurnal Teknik ITS, 2016)
Brushless DC motors have been applied extensively in household and industrial scale because of the advantages such as high efficiency and mechanical losses are low because it does not use the brush like a DC motor. Application of the brushless DC motors using 220 rms AC source is rectified to minimize battery usage. However, the use of brushless DC motors and rectifying circuit can cause poor power factor and harmonic value. Power factor value reaches 0,73 while the current THD at 74%. These values are outside the permitted tolerance limits. This study aims to improve the power factor and THD value of current caused by the operation of brushless DC motors using a SEPIC converter. Moreover, the purpose of this study is that the motor is able to operate at different levels of speed and load vary. Based on the results of the simulation from the design has been made, the motor can respond to variations in the speed reference given to well. The control circuit is also able to make the motor maintain its speed with changes in the load every time. Power factor observed in resources has increased to 0.999 at various speeds. In addition, the current THD has an average value of 2% at various speeds. Both of these parameters are within the tolerances allowed by the standard.